HHCART: An oblique decision tree - Wickramarachchi, D.C.; Robertson, B.L.; Reale, M.; Price, C.J.; Brown, J. (Computational Statistics and Data Analysis, 2015)
Attached

Decision trees are a popular technique in statistical data classification. They recursively partition the feature space into .disjoint sub-regions until each sub-region becomes homogeneous with respect to particular class. The basic Classification and Regression Tree (CART) algorithm partitions die feature space using axis parallel splits. When the true decision boundaries are no^ilignefr%itlfthe feature axes, this approach can produce a complicated boundary structure. Oblique decision trees use oblique decision boundaries to potentially simplify the^qndaryStructure. The major limitation of this approach is that the tree induction algorithm is Computationally expensive. Hence, as an alternative, a new decision tree algorithm called HHCART is presented. The method uses a series of Householder matrides to reflect the training data at each non-terminal node during tree construction. Each reflection is based on the directions of the eigenvectors from each class' covariance matrix. Considering of axis parallel splits in the reflected training data provides an efficient way of finding oblique splits in the unreflected training data. Experimental results show that the accuracy and size of HHCART trees are comparable with some benchmark methods. The appealing feature of HHCART is that it can handle both qualitative and quantitative features in the same oblique split
Keywords: Oblique decision tree; Data classification; Statistical learning; Householder reflection; Machine learning